Editorial - Michael Rose; Jonathan M. Hoffmann (Intergenerational Justice Review)
In the early 1980s, Derek Parfit used the example of a 14-year-old girl to illustrate the "non-identity problem" (NIP). The girl was about to decide whether or not to conceive a child at her age, and Parfit argued that she would not make that particular child worse off by conceiving now (although giving him a bad start in life) as opposed to waiting a few years and heaving a child as a grown-up. Since the girl’s child would not exist if it had not been born at that time, it could not blame its mother for its bad start in life, as long as it has a life worth living. The NIP has been part of the philosophical debate on intergenerational justice ever since. Does the NIP also apply beyond the biomedical? For this IGJR special issue, scholars were invited to assess the scope and relevance of the NIP in questions of climate change (C-NIP). Can future persons blame us for our (lack of) climate policies? In three contributions (Hoffmann, Nedevska, Unruh), Parfit’s 14-year-old girl is still discussed, and this question remains hotly disputed. For this controversial topic, we have been trying something new: In addition to regular peer-reviewed articles and reviews of selected new publications, we asked several researchers to share their perspectives regarding the C-NIP debate in a short opinion piece. Although we provided feedback on the submitted manuscripts, these opinions did not undergo a regular peer-review process. Being opinions, we have left it to the authors' judgment whether or not they revise their manuscripts. The IGJR editorial team would be very pleased to receive feedback from the inclined reader on this new format. The issue begins with six opinion pieces on the C-NIP, followed by two research articles by Thomas Bontly and Jasmina Nedevska, respectively, and two book reviews. In the first opinion piece, Ramon Das (Wellington, NZ) applies the C-NIP to historic injustice and argues that employing intragenerational counterfactuals – as opposed to intergenerational ones – can avoid the NIP and in some cases sustain harm claims. In the second opinion piece, Charlotte Unruh (Southampton) maintains that the C-NIP does not only apply to questions of harm, but also to questions of benefit. She suggests that solutions to the C-NIP will have to take both harm and benefit into account. The next two opinion pieces are concerned with whether remote acts and effects are causally and/or morally relevant for the identity of future humans. Jörg Tremmel (Tübingen) maintains that Parfit’s concept of causality is distinct from conceptions of causality employed in legal studies as well as in the sciences and argues that the non-identity effect of climate policies is overstated, once alternative conceptions of causality are employed. Contrarily, Jonas Harney (Saarbrücken) argues that indeed virtually every small single act may affect the identity of distant future individuals (see also Bontly). However, he points out that the C-NIP is only a problem to moral theories that employ a comparative personal view. Referring to Rawls’s veil of ignorance, Jonathan M. Hoffmann (Warwick) suggests employing a wide person-affecting view to questions of intergenerational justice. In contrast to the narrow person-affecting view that is linked to the NIP (see also Harney), it disregards the very identity of future individuals and emphasises the moral relevance of their human and citizen status. In the final opinion piece, Michael Rose (Lüneburg) shares a story of the lack of appreciation of the C-NIP outside of philosophical circles and argues that this is for a good reason. He introduces the “arbitrary status quo argument” that renders the C-NIP morally useless. Moreover – sounding the same horn as Hoffmann – he points out that in political practice, the citizens’ interests brought into political decision-making are not individualised anyway. The relevance of the C-NIP is debated in greater depth in two research articles. Discussing different arguments and methods of causal inference, Thomas Bontly (Storrs, CT) employs a difference-making perspective and shows that there is indeed a highly significant non-identity effect of climate change policies. Jasmina Nedevska (Stockholm) analyses the differences between the NIP in bioethics and the C-NIP and – drawing a parallel to a case of climate change litigation in California – argues that the C-NIP might indeed have practical political implications. To sum up, at least two questions are to be asked regarding the C-NIP: First, do climate policies (or the lack of them) affect distant future peoples’ identities in a significant way (the non-identity effect, in Bontly’s terms)? And second, is this morally and politically relevant? Addressing the first question, several contributions in this issue discuss the kind of causal reasoning the C-NIP is based upon. Whereas Bontly, Das and Harney affirm the non-identity effect and emphasise the crucial role of comparisons of (counterfactual) alternative worlds for the NIP and its concept of causation, Tremmel holds to his claim that the causal influence of a certain identity-affecting policy is often insignificant from a legal or scientific (particularly statistical) perspective. Regarding the second question, most authors (not all, though) seem to grant the NIP a certain moral and political relevance within the narrow person-affecting view. At the same time, several authors seem to allow for or even emphasise alternative ways of dealing with the C-NIP that uphold the moral relevance of the current generation’s actions with regard to future generations, among them Das, Hoffmann and Rose. What does all of this mean for Parfit’s 14-year-old girl? After all, only one thing is for sure: now in her early 50s, that woman still is a troublemaker. And most probably, she will continue to be. This special issue ends with two book reviews. First, Nicky van Dijk (Hobart, TAS) reviews “Intergenerational Equity”, edited by Thomas Cottier et al. (Brill Nijhoff 2019). The book, provided with a foreword by Edith Brown Weiss, offers a variety of authors and interdisciplinary perspectives on the topic, focusing on juridical, philosophical, historical and economic dimensions of environmental, cultural and political intergenerational equity. Second, Melissa Ihlow and Maria Lenk (Stuttgart) review “Humans in the Global Ecosystem”, edited by Pierre L. Ibisch et al. (Oekom Verlag 2019). The book provides a comprehensive, interdisciplinary and solution-oriented introduction to sustainable development.